2019
DOI: 10.1108/jima-10-2018-0206
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising the risks in Halal food supply chain: an MCDM approach

Abstract: Purpose Risk in the Halal food supply chain is considered as the failure to deliver the product which complies with Halal standards. The purpose of this paper is to identify the risk elements associated with Halal food supply chains and prioritise them appropriately towards better management. Design/methodology/approach This research used a systematic literature review to identify various risk elements in the Halal food supply chain and consolidate them with the expertise of professionals and academicians. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 75 publications
0
66
0
6
Order By: Relevance
“…It can be seen that the result for the send rate is approximately 43.5 -47.2 TPS. However, the "Create an Item ID" throughput rate decreases every iteration (the first iteration is approximately 30-31 TPS, and the second and third iterations are approximately 19-26 TPS), although the "Transfer an Item ID" throughput rate is still almost the same for all iterations of each channel (16)(17)(18)(19)(20)(21). This pattern is also different from the query pattern, which shows that the results for the query throughput rate are approximately twice the invoke throughput rate.…”
Section: Simulation Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the result for the send rate is approximately 43.5 -47.2 TPS. However, the "Create an Item ID" throughput rate decreases every iteration (the first iteration is approximately 30-31 TPS, and the second and third iterations are approximately 19-26 TPS), although the "Transfer an Item ID" throughput rate is still almost the same for all iterations of each channel (16)(17)(18)(19)(20)(21). This pattern is also different from the query pattern, which shows that the results for the query throughput rate are approximately twice the invoke throughput rate.…”
Section: Simulation Configurationmentioning
confidence: 99%
“…In addition, the term "toyyib" means healthy and good [15]. The toyyib concept can also be used to enrich society with spiritual, moral and humanitarian values, as well as food safety regulations [16]. However, the gray area (located between halal and haram) causes doubt in the application of the halal concept.…”
Section: Halal Supply Chain Managementmentioning
confidence: 99%
“…The fuzzy AHP methodology is widely acceptable by the researchers, particularly in the prioritization issues. In recent times, [ 36 ] use this methodology to prioritize the Halal food supply chain’s risk elements. In this study, the authors identified the risk elements associated with Halal supply chains using systematic literature methodology.…”
Section: Overview Of Analytical Hierarchy Process and Fuzzy Analyticamentioning
confidence: 99%
“…Table 1 presents some of the techniques found in the literature, using fuzzy set theory with MCDM techniques, that were used to select suppliers, for example, Fuzzy and AHP, Fuzzy and TOPSIS, and Fuzzy and SWARA. With regard to the supplier selection problem in the food industry, there is limited amount of literature discussing formal reference frameworks (Magdalena, 2012;Liao, 2012;Lin & Wu, 2011;Pasek, 2011;Azadnia et al, 2015;Nakandala et al, 2017;Rathore et al, 2017;Jafarzadeh Ghoushchi et al, 2019;Khan et al, 2019;Liu et al, 2019;Wang et al, 2020;Kaviani et al, 2020), especially in the Brazilian context Freitas et al, 2020) Table 1. Decision techniques for supplier selection models in the food industry.…”
Section: Multicriteria Decision-making Techniques For Supplier Selectionmentioning
confidence: 99%
“…In the literature, some relevant articles articles have used hybrid decision-making methods to select or evaluate suppliers in the food supply chain (Magdalena, 2012;Liao, 2012;Lin & Wu, 2011;Pasek, 2011;Nakandala et al, 2017;Rathore et al, 2017;Jafarzadeh Ghoushchi et al, 2019;Liu et al, 2019;Wang et al, 2020;Kaviani et al, 2020), including using the Fuzzy AHP technique (Azadnia et al, 2015;Khan et al, 2019). However, food security, when addressed, is incorporated as part of quality, not being assessed at the first level and separately as other criteria (e.g.…”
Section: Introductionmentioning
confidence: 99%